Integrated Strategies to Reduce Poverty Rate Through Innovation of E-Kembang Village and Poverty SIM in Bangka Regency and Pati Regency - Yusniah Anggraini (International Journal of Regional Innovation, 2021)
Based on Presidential Regulation of the Republic of Indonesia Number 13 of 2009 concerning the Coordination of Poverty Reduction that poverty is an urgent national problem and requires systematic, integrated and comprehensive handling steps and approaches, in order to reduce the burden and fulfill the basic rights of citizens properly to take and develop a dignified life. Therefore, this study aims to determine the extent of innovation carried out by the regions, especially Bangka Regency and Pati Regency in overcoming poverty that occurs in their area. With this research, it is hoped that it can become a bridge or facilitator for other regions in seeking innovations in the field of welfare to solve poverty so that it is not only the regions concerned that apply this innovation and can be a solution to realize more prosperous districts/cities in Indonesia. This study uses a qualitative approach. The population in this study is an area that has made innovations in order to minimize poverty that occurs in their area. While the research subjects are in Bangka Regency which has the name E-KEMBANG DESA innovation (Bangka Poverty with Systems and Applications), and Pati Regency with the name SIM POVERTY (Poverty Reduction Management Information System) innovation from Bappeda Pati. This research shows that the innovations made by the regions in minimizing poverty can support the creation of a more prosperous environment and reduce poverty in the areas where innovation occurs. In addition, one of the results of the innovation of E-KEMBANG DESA (Bangka Poverty with Systems and Applications) is that it has succeeded in making planning and budgeting documents, the acceleration of poverty reduction in Bangka Regency is sought to synergize and synchronize planning and financing. While one of the results of the innovation of SIM POVERTY (Poverty Reduction Management Information System) Bappeda Pati is the use of information technology-based so as to create data accuracy by integrating NIK.